MASYARAKAT HINDU DALAM POLITIK NKRI MENUJU MASYARAKAT SIPIL - I NENGAH DUIJA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Peoples Hinduism is one component of the whole Indonesian nation from a state (nation state). Therefore, the position and its position in the Republic of Indonesia is actually the same, but in the context of national politics often a question of what is by Antonio Gramsci as a political regional hegemony. Hegemony is happening is the issue of access to power, economic, social, cultural, religious, and even become a